PENINGKATAN KEAKTIFAN MAHASISWA PADA PROSES PEMBELAJARAN MATA KULIAH IPS 2 MENGGUNAKAN MODEL KOOPERATIF JIGSAW DALAM KEGIATAN LESSON STUDY - Siti Maisaroh (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
Lesson study activities aims to enhance the activity of students in the learning process in the course IPS 2 using cooperative learning model jigsaw in lesson study activities. Lesson study activity was conducted in Even Semester Academic Year 2012/2013. The subject is mahassiswa A1 class numbering 40 students. The procedure used in this study lesson activities through measures plan, do and see, which is implemented in four cycles. Data collection technique used observation sheets, sheet liveliness assessment and student achievement tests. While the analysis of the data using formulas liveliness and average. Lesson study activities can enhance the activity and student achievement Based on the observations that have been made, the activity of the students look more dominant on the activities of the group individually. This is shown in the increase in the activity of each cycle. In the first cycle the activity of individual students in classical gained 47.5% while the activity of the students in the group amounted to 57.5%. At silkus II activity of individual students in classical gained 52.5% while the activity of the students in the group by 71%. In the second cycle the activity of individual students in classical gained 59.5% while the activity of the students in the group by 83%. While in the fourth cycle of activity of individual students in classical gained 64.5% while the activity of the students in the group by 85%. The average achievement of students also increased, in the first cycle of learning achievement average of 72.76, the second cycle 7